Fresno Chapter of Women's International League for Peace and Freedom Celebrating Louise Erickson and Marcia McLane - Watkins, Howard::::::::: (1989)
Linda Mack, Louise Erickson reading aloud, Marcia McLane; back: Barbara Gaines and Mary Ellen Clay